Evaluation of psoriasis patients’ attitudes toward benefit–risk and therapeutic trade-offs in their choice of treatments - Eliasson, Lina (Patient Prefer Adherence, 2017)
OBJECTIVE: Treatment options for psoriasis offer trade-offs in terms of efficacy, convenience, and risk of adverse events. We evaluated patients’ preferences with respect to benefit–risk in the treatment of psoriasis. METHODS: A discrete choice experiment was conducted in adults from the UK with moderate-to-severe psoriasis using an orthogonal design with 32 hypothetical choice sets. Participants were randomly assigned to one of two surveys with 16 choice sets. Patients’ preferences were investigated with respect to the following attributes: reduction in body surface area affected by psoriasis, treatment administration (frequency and mode of delivery), short-term diarrhea or nausea risk, and 10-year risk of developing melanoma or nonmelanoma skin cancer, tuberculosis, or serious infections. A mixed effects logistic regression model generated relative preferences between treatment profiles. RESULTS: Participants (N=292) had a strong preference to avoid increased risk of melanoma or nonmelanoma skin cancer (odds ratio [OR]: 0.44 per 5% increased 10-year risk) and increased risks of tuberculosis and serious infections (both ORs: 0.73 per 5% increased 10-year risk) and preferred once-weekly to twice-daily tablets (OR: 0.76) and weekly (OR: 0.56) or fortnightly (OR: 0.65) injections. Participants preferred avoiding treatments that may cause diarrhea or nausea in the first 2 weeks (OR: 0.87 per 5% increase) and preferred treatments that effectively resolved plaque lesions (OR: 0.93 for each palm area still affected). CONCLUSION: All attributes were significant predictors of choice. Patients’ preference research complements clinical trial data by providing insight regarding the relative weight of efficacy, tolerability, and other factors for patients when making treatment choices.